The Role of Educational Level and Cognitive Status in Men Undergoing Artificial Urinary Sphincter Implantation - ONUR, AHMET RAHMİ (ELSEVIER SCIENCE INC, 2021)
OBJECTIVE To examine the relationship between education level, cognitive function of patients and the success/ revision rates of artificial urinary sphincter (AUS) implantation in men with postprostatectomy incontinence. METHODS Between January 2010 and March 2018, 163 patients (mean age, 68 +/- 6.8 years) with moderate-to-severe stress urinary incontinence who underwent AUS implantation were retrospectively examined. Demographic data, body mass index, comorbidities, surgical technique, previous strictures, and radiation therapy were recorded. Incontinence was measured by daily pad use and evaluated by International Consultation on Incontinence Questionnaire-short form. Patients' overall improvement was assessed using the Patient Global Impression of Improvement questionnaire. Education level was determined using the International Standard Classification of Education. Cognitive status was assessed using the Mini-Mental State Examination. Treatment success was defined as the need for <= 1 pad/day at last follow-up. RESULTS AUS was successful in 77.3% of patients. The International Consultation on Incontinence Questionnaire-short form score improved significantly from 19.9 +/- 2.9 to 4.4 +/- 5.4 (P = .001). The median outcome reported subjectively on the Patient Global Impression of Improvement scale was 2.1 +/- 1.5 (1-7) and self-reported as much better. Patients' education level had statistically no significant relationship with AUS success and revision rates. Similarly, there was no significant relationship between cognitive status, educational level and the need for revision of AUS (P >.05). However, patients with moderate cognitive impairment and a body mass index >30 showed significantly lower AUS success rates (P <.05). CONCLUSION AUS implantation is safe and effective treatment option especially for nonobese and cognitively intact patients of all educational levels. (C) 2020 Elsevier Inc.
Keywords: LONG-TERM OUTCOMES; INCONTINENCE; IMPACT; CLASSIFICATION; PATIENT; COHORT